Вплив магнiтної складової поля на розсiяння електромагнiтної хвилi металевим наноелiпсоїдом - Butenko, D. V.; Tomchuk, P. M. (Publishing house "Academperiodika", 2019)
The influence of the magnetic dipole moment of a non-spherical metal nanoparticle on the scattering of electromagnetic radiation by the particle has been studied in the framework of the kinetic approach. Analytical expressions for the scattering cross-section of spheroidal particles are obtained, and their dependence on the incident radiation wavelength and the nanoparticle eccentricity is analyzed. The contribution of a magnetic moment to the scattering at frequencies far from the plasmon resonance is shown to be comparable with that of the electric moment, with the ratio between the magnetic and electric moment contributions being maximum for spherical nanoparticles. The calculations are performed for an arbitrary ratio between the particle size and the free electron path, which enables our results to be compared with the Mie theory in the case where the electron scattering in the particle bulk dominates.